The power of supportive parenting on children’s mathematical performance: evidence from a longitudinal study - Xue Wang; Kunshuo Du; Meizhen Zhao; Yi Ma; Shuang Zang (Scientific Reports, 2024)
Abstract Mathematical performance, a competitive edge for children, has received ample attention from stakeholders, especially from parents. However, the association between parenting style and children’s mathematics performance remains open to debate, and longitudinal studies are lacking. Therefore, this study used longitudinal data from four waves of surveys (2012, 2014, 2016, and 2018), with an initial sample of 1042 children (51.5% girls) aged 11, 13, and 15 years. Positive associations between supportive parenting style and higher mathematics scores were observed across all waves, both in unadjusted and adjusted generalized linear regression models, with all p < 0.05. Even after running five sets of sensitivity analyses (e.g., controlling counting skills in toddlerhood, imputing key covariates), the positive association remained robust. Ultimately, we found that supportive parenting style was positively associated with improved mathematical performance in adolescents measured up to six years later. This finding underscores the importance of supportive parenting in enhancing adolescents’ mathematical performance and suggests that integrating supportive parenting strategies into family-based approaches may effectively improve children’s mathematical achievements.